2022
DOI: 10.1186/s40792-022-01468-9
|View full text |Cite
|
Sign up to set email alerts
|

Left hepatectomy with suprahepatic inferior vena cava resection and reconstruction under veno-arterial extracorporeal membrane oxygenation for intrahepatic cholangiocarcinoma: a case report

Abstract: Background Curative surgery is the most effective treatment for intrahepatic cholangiocarcinoma (ICC). When an ICC involves the suprahepatic inferior vena cava (IVC), hepatectomy with suprahepatic IVC resection and reconstruction is challenging. For reconstruction of the suprahepatic IVC, total hepatic vascular exclusion (THVE), veno-venous bypass, and/or in situ hypothermic portal perfusion are required, but mortality and morbidity remain high. Case presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Intraoperative bleeding during hepatectomy, and subsequently need for blood transfusion are important predictors of adverse perioperative outcomes [ 3 , 21 ]. This meta-analysis identified that combination of IIVCC and PM is an effective surgical strategy to limit intraoperative blood loss and need for IOBT in comparison to PM alone approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative bleeding during hepatectomy, and subsequently need for blood transfusion are important predictors of adverse perioperative outcomes [ 3 , 21 ]. This meta-analysis identified that combination of IIVCC and PM is an effective surgical strategy to limit intraoperative blood loss and need for IOBT in comparison to PM alone approach.…”
Section: Discussionmentioning
confidence: 99%
“…During major hepatic resection, intraoperative blood loss may range from 200 to 2000 mL, with approximately 25.2–56.8% of patients requiring intraoperative blood transfusion [ 1 , 2 ]. Several studies have identified intraoperative blood loss and transfusions, during hepatectomy, as significant risk factors for perioperative morbidity and mortality [ 3 ]. Therefore, it remains crucial to identify and implement interventions to minimize intraoperative bleeding during hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, tumor resection with vascular reconstruction is now being performed [ 6 ]. In some cases, extracorporeal circulation is used for resection of tumors that have invaded more centrally than the hepatic vein [ 7 ]. In addition to tumor resection and vascular reconstruction by standby surgery as described above, we are sometimes requested to perform repair due to unexpected vascular injury during surgery.…”
Section: Discussionmentioning
confidence: 99%